Investigation of the periodic solutions of nonlinear autonomous systems in the critical case - Korol', I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We analyze the conditions of existence and the numerical-analytic method for the approximate construction of periodic solutions of nonlinear autonomous systems of differential equations in the critical case.